International Indices: Measurement and Usage Issues - Sierova Iryna A. (Problemi Ekonomiki, 2020)
The article considers the correctness of the construction of international indices and the possibility of their use in analytical practice. The interconnection of such concepts as: assessment of accuracy of source information – assessment of accumulation of errors during its processing – assessment of accuracy of quantitative estimates obtained based on analysis of main advantages and disadvantages of international indices, is tracked. The emphasis is made on scaling as a method that allows combining the general principles of mathematical analysis and specific methods of data collection. The expediency of selecting a method of data conversion during the transition from the ordinal scale to the interval one is determined, which is a necessary condition for the possible comparability of ranking positions in the presence of various research objectives and arrays of the data collected. The relationship between the methods of data classification as the basis of their primary systematization is considered. To determine the possibility of comparing international indices with regard to the general characteristics of a cluster and the changes within this cluster, the method of cross-clustering is used. The issues of the correctness of aggregate estimates are raised.There proved the erroneousness of revealing dynamic patterns at failing to meet the conditions when the quality of the research tools used is determined by their validity and reliability, and the quality of the results obtained is determined by the accuracy of measurements,. It is found that the stability of the socio-economic system should be confirmed by the statistical stability of the indicators that characterize this system. A scheme of relationships of requirements for data in the construction of international indices is proposed.